Origins of tropospheric ozone interannual variation over Réunion: A model investigation. Issue 1 (8th January 2016) - Liu, Junhua; Rodriguez, Jose M.; Thompson, Anne M.; Logan, Jennifer A.; Douglass, Anne R.; Olsen, Mark A.; Steenrod, Stephen D.; Posny, Françoise
Abstract: Observations from long‐term ozonesonde measurements show robust variations and trends in the evolution of ozone in the middle and upper troposphere over Réunion Island (21.1°S, 55.5°E) in June–August. Here we examine possible causes of the observed ozone variation at Réunion Island using hindcast simulations by the stratosphere‐troposphere Global Modeling Initiative chemical transport model for 1992–2014, driven by assimilated Modern‐Era Retrospective Analysis for Research and Applications meteorological fields. Réunion Island is at the edge of the subtropical jet, a region of strong stratospheric‐tropospheric exchange. Our analysis implies that the large interannual variation (IAV) of upper tropospheric ozone over Réunion is driven by the large IAV of the stratospheric influence. The IAV of the large‐scale, quasi‐horizontal wind patterns also contributes to the IAV of ozone in the upper troposphere. Comparison to a simulation with constant emissions indicates that increasing emissions do not lead to the maximum trend in the middle and upper troposphere over Réunion during austral winter implied by the sonde data. The effects of increasing emission over southern Africa are limited to the lower troposphere near the surface in August–September. Key Points: The GMI‐CTM Model simulated the main features of the observed ozone IAV over Réunion Stratospheric input plays an important role in the tropospheric ozone IAV over Réunion Changes in emissions have little influence on middle and upper tropospheric ozone over Réunion